2021
DOI: 10.1021/acsanm.1c01889
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica-Coated CsPbX3 Nanocrystals with High Stability and Ion-Exchange Resistance for Bright White-Emitting Displays

Abstract: All-inorganic metal halide perovskite (CsPbX 3 ) nanocrystals (NCs) have attracted much attention due to their excellent photoelectric properties. However, CsPbX 3 NCs are easily affected by polar solvents because of their ionic crystal nature, which led to luminescence quenching. In this paper, mesoporous silica nanoparticles (MSNs) were used as carriers to anchor CsPbX 3 NCs for effectively improving the resistance of CsPbX 3 NCs in polar solvents. CsPbX 3 @MSN composites were created via a sol−gel-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…While the majority of the time, these PNCs are used in photovoltaics, photodetectors, and light-emitting diode (LED) devices, only limited research has been done toward photocatalysis. Apart from carrier diffusion, the crystalline nature, energy levels, and exciton binding energies of halide perovskites have played an essential role in efficient charge separation . Recently, PNCs have been used as photocatalysts by Park et al in signifying H 2 evolution from a saturated hydroiodic acid solution in the presence of MA–lead iodide perovskite as the photocatalyst to advance the reaction mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of the time, these PNCs are used in photovoltaics, photodetectors, and light-emitting diode (LED) devices, only limited research has been done toward photocatalysis. Apart from carrier diffusion, the crystalline nature, energy levels, and exciton binding energies of halide perovskites have played an essential role in efficient charge separation . Recently, PNCs have been used as photocatalysts by Park et al in signifying H 2 evolution from a saturated hydroiodic acid solution in the presence of MA–lead iodide perovskite as the photocatalyst to advance the reaction mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…The decay components for 10% Bi-doped CsPbBr 3 NCs are as follows: τ 1 = 0.6 ns (89%), τ 2 = 2.1 ns (9%), and τ 3 = 14 ns (2%) with an average lifetime of 1.0 ± 0.1 ns. The τ 2 component arises due to the excitonic recombination process, and the other two components (τ 1 and τ 3 ) are associated with the trap-mediated radiative recombination process. The analysis shows that the τ 1 and τ 3 components significantly decrease with an increase in their amplitude due to the incorporation of Bi into CsPbBr 3 NCs. This suggests that the trap-mediated relaxation pathway for the charge carriers increases upon Bi doping.…”
mentioning
confidence: 99%
“…20 Shi et al demonstrated that CsPbX 3 NCs were anchored to the carrier mesoporous silicon nanoparticles to prevent perovskites from being damaged in polar solvents. 21 Hu and co-workers prepared the CsPbX 3 /SiO 2 and CsPbBr 3 /Ta 2 O 5 Janus nanoparticles via a water trigger method and sol−gel approach, respectively, which effectively improved the stability of NCs. 22 Li et al successfully synthesized the CsPbBr 3 silica/alumina monolith by the sol−gel method, which has amazing stability and high luminescence in toluene.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, in the metal organic framework, the color of the materials itself affects luminescence of perovskite materials. The conventional inorganic coating materials include SiO 2 , Ta 2 O 5 , TiO 2 , and alumina and also are used as the matrix material. Yang’s group synchronously achieved the successful preparation of CsPbBr 3 @SiO 2 core–shell nanoparticles and Janus structure, enhancing its stability under humid conditions .…”
Section: Introductionmentioning
confidence: 99%